Análisis de la campaña transmedia en el programa televisivo de Juegos de Tronos. Una propuesta para el medio local - Naula Mazón, Andrea Alexandra (2016)
The new ways to communicate and interact through the social media, is aiming for the traditional ways to tell a story in a single media to reproduce and multiply this stories to grow to a one fictional world in which the TV audience is waiting an willing to participate in an active environment when the media is put on the test to answer to this new road of communication. Local series has invest his affords to direct the audience to consume and follow their favorite TV programs in the social media channel, but unfortunately this hasn’t been approached in an optimum way. In fact the audience tries to connect and follow for the content of this fan pages created by the TV channel for their local production but only in their first steps to conquer and make a functional world between the traditional TV and the digital Medias. This investigation has as objectives to propose several tools to migrate from the traditional TV narrative to the transmedia narrative in a practical way making a contrast with the analysis of the Game of Thrones TV series transmedia campaign created for the first season of the show. In order to suggest punctual ideas to create new content and amplify the reach of the local TV production and make it more rentable and effective the way they are conquering the old and new audience of an specific production in Guayaquil city.